NMR espectroscopic parameters of HX and Si (Sn)X4 (X = H, F, Cl, Br and I) and SnBr4-nIn model compounds - Maldonado, Alejandro Fabián (2012)
The NMR spectroscopic parameters are largely influenced by relativistic effects. They are highly dependent on the electronic behavior inside the spatial regions occupied by nuclei. Full relativistic calculations of indirect nuclear spin-spin couplings at random phase level of approach (RPA) in the title compounds with reoptimized Dyall cVTZ basis sets are given. A comparison with the results of calculations with other basis sets that are mostly used within the non-relativistic (NR) domain is presented. We analyzed the dependence of that couplings with the speed of light over the whole range of values, from the full relativistic to the NR regimes. Within this last regime, calculations at the second-order level of approach (SOPPA) indicated that electron correlation effects may not be as important for nuclear magnetic shieldings, but they must be included with care for J-coupling calculations. From these calculations, we determined that relativity enlarges the electron correlation effects of the J-couplings of HBr and HI. Because the results of nuclear magnetic shielding calculations within polarization propagators at the RPA level were reliable, we were able to show a new and easy procedure to obtain absolute nuclear magnetic shieldings on reference compounds for both Si and Sn nuclei: σ[Si (CH 3) 4] = 421.28 ± 29.33 ppm and σ[Sn (CH 3) 4] = 3814.96 ± 79.12 ppm. They were obtained from experimental chemical shifts and accurate nuclear magnetic shielding calculations on different molecular systems.